(untitled) (Scientific journal of the Fergana State University, 2025)
This study focuses on examining the content and methods of developing logical thinking in future educators of upbringing. The research discusses the importance of logical thinking in education and methods for its development through pedagogical technologies. Special attention is given to methods such as interactive teaching, problem-based learning, and others that foster the development of logical thinking.